(untitled) (SALAM Digest: Syariah and Law Undergraduate Symposium, 2023)
Misyar Marriage, a non-traditional form of marital contract, has gained attention within the Malaysian Muslim community due to its flexible nature, allowing couples to waive or modify certain marital obligations, such as cohabitation and financial support. While this arrangement offers an alternative to conventional marriage, its compatibility with Syariah Law and its impact on the institution of marriage in Malaysia remain subjects of significant debate. This research examines the legal status of Misyar Marriage under Malaysian Syariah Law, exploring whether it aligns with Islamic principles and the extent to which it is practiced. Additionally, the study analyzes the implications of Misyar Marriage on family dynamics, considering potential challenges such as the erosion of marital stability and the welfare of children born from such unions. By reviewing legal texts, scholarly interpretations, and real-life cases, this research aims to provide a thorough understanding of Misyar Marriage’s place within Malaysian society. The findings seek to contribute to the ongoing discourse by offering recommendations for more balanced and sustainable practices, ensuring that any adaptation of Misyar Marriage within Malaysia remains in harmony with the core values of Islam and supports the well-being of families.